FY 2016 Kosovo Country Opinion Survey - World Bank Group (World Bank, Washington, DC, 2017)
The Country opinion survey for 2016 in Kosovo assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Kosovo perceive the WBG. The survey explored:(i) general issues facing Kosovo; (ii) overall attitudes toward the World Bank Group; (iii) World Bank Group’s effectiveness and results; (iv) The World Bank Group’s knowledge work and activities; (v) working with the World Bank Group; (vi) the future role of the World Bank Group in Kosovo; (vii) communication and information sharing; and (viii) background information.